1994
DOI: 10.1213/00000539-199407000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pH-Adjusted Bupivacaine 0.75% and a Mixture of Bupivacaine 0.75% and Lidocaine 2%, Both with Hyaluronidase, in Day-Case Cataract Surgery Under Regional Anesthesia

Abstract: Alkalinized bupivacaine 0.75% (pH 6.8) and a mixture (1:1) of bupivacaine 0.75% and lidocaine 2%, both with hyaluronidase, were compared in regional ophthalmic anesthesia for day-case cataract surgery. Eighty-two patients were randomized into two groups (n = 39 and 43) to receive one of the two solutions in a double-blind manner. Two intraorbital injections were administered initially: an inferolateral intraconal injection (3 mL) and a medial extraconal injection (3.5 mL). The progress of lid and globe akinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 0 publications
0
10
1
2
Order By: Relevance
“…6 Considering these known facts, a number of clinical trials for ocular procedures using retrobulbar or peribulbar techniques have been conducted with a variety of LA combinations and strengths, together with hyaluronidase and pH adjustment, to determine optimum mixtures. [4][5][6][7][8]17 In our study, we could not find any difference in the time to onset and time to full akinesia between the LBH-pH and LBH groups ( Table 2). This finding does not agree with the results obtained using other block techniques.…”
Section: Table 1 Scoring Systemcontrasting
confidence: 51%
“…6 Considering these known facts, a number of clinical trials for ocular procedures using retrobulbar or peribulbar techniques have been conducted with a variety of LA combinations and strengths, together with hyaluronidase and pH adjustment, to determine optimum mixtures. [4][5][6][7][8]17 In our study, we could not find any difference in the time to onset and time to full akinesia between the LBH-pH and LBH groups ( Table 2). This finding does not agree with the results obtained using other block techniques.…”
Section: Table 1 Scoring Systemcontrasting
confidence: 51%
“…We found similar rates of diplopia the day after surgery in the two groups (26% in the ropivacaine group and 30% in the bupivacaine/lignocaine group). The incidence for ropivacaine is intermediate between that reported for bupivacaine 0.75% alone (70%) and the 8% incidence with lignocaine 2% and bupivacaine 0.75% reported in one series [21]. It is not known whether a weaker concentration of ropivacaine would provide adequate akinesia for surgery without such a high incidence of diplopia.…”
Section: Discussionmentioning
confidence: 66%
“…On direct questioning 40% of group L and 52% of group B reported double vision when the eye shield was removed the morning after surgery. Sarvela et al reported that 70% of patients receiving 0.75% bupivacaine for retro/peribulbar anaesthesia experienced diplopia the following day, whereas a mixture of 0.75% bupivacaine and 2% lignocaine resulted in a diplopia rate of 8% [21]. Prolonged diplopia represents a significant risk to elderly patients who may already have impaired mobility.…”
Section: ¹1mentioning
confidence: 99%